PENGARUH PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN PT MULTIELOK COSMETIC - Mukhammad Adieb (Journal Of Communication Education, 2016)
ABSTRACT Various studies show career development and compensation are the factors that affect work motivation. Employees who are not satisfied with career development and compensation are obtained it will affect motivation, which in turn will impact on the level of contribution to the company.This study aimed to examine the influence of career development variables and variable compensation to variable motivation. The method used in this study is a descriptive survey method, a method that describes the circumstances or events during the study by recording and analyzing the conclusions are then drawn. To obtain the data in the study, the samples used were 275 people from 875 employees. Sampling technique using stratified random sampling technique. Because the population is heterogeneous. In this case I took the sample through the levels of education. Instruments used in the form of questionnaire, interviews, and observations. Then the data obtained in the test media quantitatively through SPSS 20 to prove the hypothesis made. From the analysis of the data found that career development and a significant positive effect on motivation. In addition, compensation and significant positive effect on motivation. When tested together, then 45.8% of the variance of Career Development and Compensation can be explained by changes in the variable motivation. The remaining 54.2% is influenced by other variables Keywords: Career Development, Compensation and Motivation.